2022
DOI: 10.1111/brv.12889
|View full text |Cite
|
Sign up to set email alerts
|

How climate, topography, soils, herbivores, and fire control forest–grassland coexistence in the Eurasian forest‐steppe

Abstract: Recent advances in ecology and biogeography demonstrate the importance of fire and large herbivoresand challenge the primacy of climateto our understanding of the distribution, stability, and antiquity of forests and grasslands. Among grassland ecologists, particularly those working in savannas of the seasonally dry tropics, an emerging fire-herbivore paradigm is generally accepted to explain grass dominance in climates and on soils that would otherwise permit development of closed-canopy forests. By contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 161 publications
0
9
0
Order By: Relevance
“…The results of recent studies suggest that both views can be reconciled if we take into consideration all major factors driving forests-steppe development, i.e. climate, topography, soil and disturbance regime (Chytrý, et al 2022; Erdős et al, 2022). The synthesis of Feurdean et al (2018), based in part on case studies from the Transylvanian Basin, proposed a general model of Holocene grassland persistence in the East-Central European lowlands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of recent studies suggest that both views can be reconciled if we take into consideration all major factors driving forests-steppe development, i.e. climate, topography, soil and disturbance regime (Chytrý, et al 2022; Erdős et al, 2022). The synthesis of Feurdean et al (2018), based in part on case studies from the Transylvanian Basin, proposed a general model of Holocene grassland persistence in the East-Central European lowlands.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of open and semi-open ecosystems in potentially forested landscapes raises questions about their origin and long-term dynamics. In addition to climate, other possible driving factors such as topography and especially the disturbance regime come to the fore (Chytrý et al, 2022; Erdős et al, 2022; Sümegi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the extensive European forest‐steppe region harbours several deciduous tree species characterized by relatively higher resource‐acquisitive strategies, including Tilia cordata , Ulmus glabra and Populus tremula (Erdős et al., 2018). Hence, the wider distribution of these species could be linked to their relatively faster growth rate favoured by milder climatic conditions characterizing the Eurasian forest‐steppe mosaics (Erdős et al., 2022) compared, for example, to the drier Mediterranean climate.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Protection from fire Fire has a significant impact on various aspects of plant performance and functioning, prompting plants to evolve diverse traits for adaptation, particularly in environments prone to frequent fire, such as grass-dominated habitats (He, Lamont & Pausas, 2019;Erd} os et al, 2022). Recent research conducted by Simpson et al (2021) has demonstrated that awns of grass play a crucial role in fire protection through their ability to enhance seed burial.…”
Section: Adaptation To Abiotic Environmentsmentioning
confidence: 99%
“…Fire has a significant impact on various aspects of plant performance and functioning, prompting plants to evolve diverse traits for adaptation, particularly in environments prone to frequent fire, such as grass‐dominated habitats (He, Lamont & Pausas, 2019; Erdős et al ., 2022). Recent research conducted by Simpson et al .…”
Section: Adaptation To Abiotic Environmentsmentioning
confidence: 99%